2021
DOI: 10.1111/iwj.13581
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of nurses in intensive care unit on preventing medical device–related pressure injury: A cross‐sectional study in western China

Abstract: The knowledge, attitude, and practice of nurses in intensive care units (ICUs) are determinants for the efficacy of preventing the medical device-related pressure injury (MDRPI). The aim of this study was to determine the level and factors of knowledge, attitude, and practice of nurses' ICUs on preventing medical MDRPI in western China. An annual cross-sectional study was conducted in hospitals of western China from May 2020 to September 2020.Nurses' knowledge and attitudes were assessed using Clinical Nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
48
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 20 publications
9
48
2
1
Order By: Relevance
“…Attitude scores were highest in subjects with 16 to 20 years of work experience. 22 This is inconsistent with the current study, where work experience had a significant impact on the level of attitude regarding sepsis and sepsis management, but those with 15 years or more had the lowest mean attitudes compared to other participants. Another study published in Indonesia (2016) showed that positive attitudes in nurses and physicians were critical in emergency practice, as they have a direct impact on the quality, safety, accountability, and responsibility of care.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Attitude scores were highest in subjects with 16 to 20 years of work experience. 22 This is inconsistent with the current study, where work experience had a significant impact on the level of attitude regarding sepsis and sepsis management, but those with 15 years or more had the lowest mean attitudes compared to other participants. Another study published in Indonesia (2016) showed that positive attitudes in nurses and physicians were critical in emergency practice, as they have a direct impact on the quality, safety, accountability, and responsibility of care.…”
Section: Discussioncontrasting
confidence: 95%
“…A study published in Western China (2021) showed that the scores of attitudes and practices can predict the knowledge level regarding the prevention of medical device-related pressure injury ( P < .005). 22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scale consists of four sections, with items on sociodemographic data, 15 items on knowledge, 9 questions on attitudes, and 14 on prevention practice. Responses were presented on a 5point Likert-type scale, ranging from 38 to 190.The higher the score, the higher the levels of prevention 50 .…”
Section: Discussionmentioning
confidence: 99%